Aggravating and protective factors in patients’ experiences of vulvodynia: a qualitative study with Italian women - Lorenzo Montali; Chiara Bernareggi; Valeria Crispiatico (BMC Psychology)
Abstract Background Vulvodynia, a chronic pain condition affecting 15% of women aged 18–70, significantly impacts daily life and sexual functioning, contributing to self-perception issues, depression, and anxiety. This study aims to explore Italian womens’ experiences, recognizing the influence of cultural background on their perceptions of chronic pain and sexual problems. Additionally, this research explores the role of family support and autoeroticism in managing vulvodynia. Methods A total of 35 interviews were conducted with women diagnosed with vulvodynia. The transcripts of these interviews were then subjected to reflexive thematic analysis. Results The analysis identified four themes: A Disabling pain; Aggravating factors: lack of support and delegitimization; Protective factors: experiences of sexual agency and relational support; Identity in reconstruction: an incomplete woman. Discussion This study confirmed a lack of medical knowledge, hindering accurate diagnosis and treatment. Women’s unmet expectations of family support amplified their sense of abandonment. Two factors reduced the burden of the disease. First, women were able to find alternatives to penetrative sex, gaining more confidence in themselves and their sexuality. Second, they developed empowering relationships in online patient groups where they were able to access valuable information and receive emotional support. This study underscores the necessity of multidisciplinary care for women with vulvodynia, addressing their various needs. Conclusions Psychological interventions involving partners and families can mitigate women’s delegitimization, and treatments centered on autoeroticism can promote women’s overall well-being.